Fischer's ratio and DNA damage in hypoxemia-induced brain injury in rat model: prophylactic role of quercetin and mexamine supplementation. - Mai O Kadry; Hanaa Ali (PLoS ONE)
Hypoxemia brain injuries arise when the brain's oxygen supply is restricted. Brain cells gradually die and become impaired as a result of the restricted oxygen flow a diversity of signaling pathways are involved in the pathophysiology of brain damage. One of the main concerns when examining the rate of protein breakdown is the measurement of the serum amino acid ratio. Valine, leucine, and isoleucine make up branched-chain amino acids, while phenylalanine and tyrosine make up aromatic amino acids. A vital tool for assessing the severity of hypoxemia is Fischer's ratio. The goal of this article is to determine how quercetin (QUR) and/or mexamine (MEX) prevented synfat (SN)-induced brain damage in a rat models. It also aimed to elucidate the various cross-linked inflammatory pathways, DNA damage, and Fischer's ratio. Following QUR and MEX therapy, synfat-induced hypoxemia. Hemoglobin (Hb) levels were markedly reduced by synfat-intoxication, and oxidative stress and inflammatory biomarkers, including TNF-??, MDA, interleukin-6 (IL-6), and C -reactive protein (CRP), were elevated. Hemoglobin levels, oxidative stress biomarkers, and the aberrant expression of pro-inflammatory cytokines were all altered by QUR and/or MEX therapy. Similarly, the concentration of γ-aminobutyric acid, serotonine, noradrenaline, and intropin in cerebral tissue is restricted. Similarly, the COMET assay and 8-oxo-7,8-dihydro-2'-deoxyguanosine analysis (8-oxodG) demonstrated that QUR and MEX potentially altered synfat-induced brain DNA damage. The results confirmed the potential impact of this combined strategy as a powerful therapy for brain hypoxemia, concluding that treatment via QUR with MEX was superior therapy in modulating synfat-triggered cerebral injury.